Job Satisfaction Among Nurses Employed in Supplementary Healthcare Models, a Qualitative Descriptive Study - Hannah Sharrock; Joanna Petrunic; Debra Kerr; Shane Crowe; Lisa Gatzonis; Bodil Rasmussen (Nursing Open)
ABSTRACT Aim This study explored workplace satisfaction for nurses employed in the supplementary employment models. Design A qualitative descriptive methodology was used. Methods Data were collected using individual semi‐structured interviews with 10 nurses employed in supplementary employment models. A thematic analysis was used. Findings Analysis revealed four key themes related to job satisfaction: (1) Professional development, education, and training shape job satisfaction; (2) The influence of variability in work practice environments; (3) Distant work relationships affect communication and organisational support and (4) Work flexibility. These themes collectively illustrate the complex interplay of factors impacting nurses' experiences and job satisfaction in supplementary employment. Conclusions Supplementary employment models provide nurses with valuable flexibility and employment opportunities. However, there are barriers for nurses in communicating with organisational leadership through formal channels and in their contribution to improve the work environment and team culture with wards and departments. To improve job satisfaction for nurses employed in supplementary roles, strategies are needed to enhance access to education and training, strengthen communication and connection with clinical teams and leadership, and establish effective feedback mechanisms.